Immersion Heats of Active Carbons in Water and Organic Substances - M.L. Goubkina; N.S. Polyakov; L.I. Tatarinova (Adsorption Science & Technology, 1993)
The immersion heats of two active carbon (AC) samples in water and organic substances with molecules of different size have been investigated. A molecular sieve effect was established. It has been shown that changes in the immersion heats of the active carbons correspond to pore structure characteristics such as the size distribution of the micropores. The immersion heats of moistened active carbons in liquids have also been investigated, and the heat balance of the process calculated.